Analysis of the Role of Teachers as Facilitators in Increasing Children's Creativity in Fine Arts Subjects at SDN 1 Senaru - Andriatno, Yulian; Habiburrahman, Lalu; Hadi, Rusman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to analyze the role of teachers as facilitators in increasing children's creativity in fine arts subjects. Creativity is an important aspect in children's development that can be developed through learning fine arts. This research was carried out at SDN 1 Senaru, Batuqok Hamlet, Senaru Village, Bayan District, North Lombok Regency. The object of the research is an analysis of the role of teachers as facilitators in increasing children's creativity in fine arts subjects in grade 5 elementary school. In this research, qualitative methods were used with a case study approach in several elementary schools. Data was collected through observation, interviews and documentation. The research results show that teachers who act as facilitators are able to create a learning environment that supports children's exploration and self-expression. Teachers give children the freedom to experiment with various art media and techniques, and encourage children to think critically and innovatively. In conclusion, the role of the teacher as a facilitator is very important in the fine arts learning process to develop children's creativity. Recommendations are provided for teacher training in implementing effective facilitation strategies.